2014
DOI: 10.1186/2190-8567-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Goodness-of-Fit Tests and Nonparametric Adaptive Estimation for Spike Train Analysis

Abstract: When dealing with classical spike train analysis, the practitioner often performs goodness-of-fit tests to test whether the observed process is a Poisson process, for instance, or if it obeys another type of probabilistic model (Yana et al. in Biophys. J. 46(3):323–330, 1984; Brown et al. in Neural Comput. 14(2):325–346, 2002; Pouzat and Chaffiol in Technical report, http://arxiv.org/abs/arXiv:0909.2785, 2009). In doing so, there is a fundamental plug-in step, where the parameters of the supposed underlying mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 52 publications
(138 reference statements)
0
80
0
Order By: Relevance
“…The proof is an easy adaptation of Theorem 2 of [1], which is originally stated for n = 1, to the case of n multivariate Hawkes processes (see also [13]). …”
Section: Lasso Estimatementioning
confidence: 98%
See 3 more Smart Citations
“…The proof is an easy adaptation of Theorem 2 of [1], which is originally stated for n = 1, to the case of n multivariate Hawkes processes (see also [13]). …”
Section: Lasso Estimatementioning
confidence: 98%
“…A more extensive study can be found in [1] and an application on real neuronal data has been done in [13].…”
Section: Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hawkes processes provide good models of this synaptic integration phenomenon by the structure of their intensity processes, see (1) below. We refer to Chevallier et al (2015) [7], Chornoboy et al (1988) [8], Hansen et al (2015) [24] and to Reynaud-Bouret et al (2014) [35] for the use of Hawkes processes in neuronal modeling. For an overview of point processes used as stochastic models for interacting neurons both in discrete and in continuous time and related issues, see also Galves and Löcherbach (2016) [22].…”
Section: Introductionmentioning
confidence: 99%